Simulation of a pumped stormwater system and evaluation of the solar potential for pumping / Hasan Huseyin Coban - Coban, Hasan Huseyin (Universiti Teknologi MARA Cawangan Sarawak, 2023)
Renewable energy investments are increasing in countries that want to reduce their dependence on foreign energy and prevent damage to nature. As the request for green vitality generation is emerging, specialists over the globe have been attempting to generate power with better approaches. Rainwater harvesting can also be a non-conventional energy source, just like wind and solar energy. Generating energy, even on a small scale, can reduce environmentally harmful and costly methods of energy production. Various endeavours have been made so far to generate electricity using rain, one of the world's most abundant resources; however, this may be one of the most compelling studies. The goal of this study is to provide electricity from rainwater in areas with a lot of rainfall but minimal electricity.